The U.S. Versus The World? How American Power Seems to the Rest of Us - Evans, Gareth (Tufts Archival Research Center, 2005)
Volume 27, Issue 2. Summer/Fall ï¿½Just about everything the U.S. doesï¿½or chooses not to doï¿½makes an enormous difference to everyone else,ï¿½ says the former Foreign Minister of Australia and current president of the International Crisis Group. If the U.S. is to enjoy its power, it might want to make friends, rather than enemies, with other nations.